Nevus Lipomatosus Superficialis with a Folliculosebaceous Component: Report of 2 Cases. (4th April 2011) - Bancalari, Eugenia; Martínez-Sánchez, Diego; Tardío, Juan C.
Abstract : Nevus lipomatosus superficialis (NLS) is an uncommon hamartomatous lesion of the skin characterized by the presence of clusters of mature fat cells among the collagen bundles of the dermis. Usually, the number of adnexal structures is reduced in NLS as compared to the normal adjacent skin, but their morphology is not altered. Nevertheless, in some instances, associated pilar abnormalities have been reported. We here report 2 cases of NLS with disorganized pilosebaceous units. The follicular structures were dilated and showed infundibular type keratinization and there were numerous mature sebaceous lobules radiating from them resembling the histology of a folliculosebaceous cystic hamartoma (FSCH) or a sebaceous trichofolliculoma. Only 2 cases of NLS with FSCH have been previously reported. Our cases represent examples of a very rare hamartomatous cutaneous lesion composed of mesenchymal and epithelial components.